Risk Management of the Implementation of Baitul Maal Wa Tamwil Based on the Regulation of the Minister of Cooperatives and SMEs No. 12 of 2023: Evidence of the Existence of Islamic Finance - Nabila Erlyanti (Athallah Publishing Globalindo, 2025)
BMT NU Gambiran Branch was established in 2021 and functions as a non-bank Islamic financial institution with the principle of Islamic savings and loan cooperatives. By providing various types of financing, this organization seeks to improve the community's economy. However, the financing provided is not free from potential risks, especially the risk of problematic financing. This study aims to analyze the implementation of risk management at BMT NU Gambiran Branch and identify mitigation steps taken to address risks based on the provisions of KEMENKOP 2023. To gain an understanding of the implementation of risk management in problematic financing situations, this study uses a qualitative approach and case studies. With primary and secondary data sources, the data collection process is carried out through interviews, observations, and documentation. Data analysis was carried out using a risk register form by the provisions of the Regulation of the Minister of Cooperatives and Small and Medium Enterprises (KEMENKOP-UKM) Number 12 of 2023 to identify, assess, and monitor the risks faced by BMT. Through risk identification, monitoring, and control, BMT NU Gambiran Branch seeks to minimize the risk of bad financing that can hinder the performance of the institution. The results of the study indicate that effective risk management can help institutions achieve optimal results and ensure the continuity of their operations.